Low-dimensional nanomaterial saturable absorbers for ultrashort-pulsed waveguide lasers - Jiang, Xiantao; Gross, Simon; Withford, Michael J.; Zhang, Han; Yeom, Dong Il; Rotermund, Fabian; Fuerbach, Alexander (Optical Materials Express, 2018)
A wide range of saturable absorbers composed of novel low-dimensional nanomaterials were fabricated, and their linear and nonlinear optical properties were characterized. Furthermore, their suitability for ultrashort-pulse generation in waveguide laser operating at a wavelength of 2 microns was demonstrated and passively q-switched modelocked operation was achieved with all absorbers. The material systems that were studied in this work include nanosheet-based absorbers composed of graphene, carbon nanotubes, black phosphorus, transition-metal dichalcogenides, topological insulators and indium tin oxide. By utilizing a uniform few-layer spin coating fabrication technique and by employing a single, identical laser resonator, a direct comparison of the individual characteristics of these materials in the context of short-pulse generation in waveguide lasers was made possible. Each of the individually fabricated and characterized saturable absorbers was placed inside a thulium-doped fluoride glass waveguide chip laser cavity and the resulting output performance was analyzed and contrasted. It was further found that the few-layer spin coating approach enables fine-tuning of the absorber characteristics and that all low-dimensional nanomaterials under investigation can be utilized for ultrashort pulse generation in the 2-micron wavelength range. General guidelines for the design of passively modulated shortpulsed laser oscillators are presented based on those findings.
Keywords: Fabrication technique; Individual characteristics; Linear and nonlinear optical properties; Passively Q-switched; Short pulse generation; Topological insulators; Transition metal dichalcogenides; Ultrashort pulse generation